Propuesta de diseño arquitectónico para albergue de rescate animal en la ciudad de Guayaquil - Lanche Vélez, Teddy Estuardo (2023)
This research paper proposes to design an animal rescue shelter in the city of Guayaquil, strategically located in Los Vergeles, this sector has a mix of residential and commercial spaces, families find a variety of economic opportunities through commercial activities and services. Currently this area does not have pet shelters, this type of equipment is essential, not only to improve the quality of life of the animals but also of the people in the sector. The project seeks to meet the needs of animals and people...........